Degree of handedness and priming: further evidence for a distinction between production and identification priming mechanisms - LaVoie, Donna J.; Olbinski, Brianna; Palmer, Shayna (Frontiers in Psychology, 2015)
The distinction between implicit and explicit forms of memory retrieval is long-standing, and important to the extent it reveals how different neural architecture supports different aspects of memory function. Similarly, distinctions have been made between kinds of repetition priming, a form of implicit memory retrieval. This study focuses on the production-identification priming distinction, which delineates priming tasks involving verification of stimulus features as compared to priming tasks that require use of a cue to guide response retrieval. Studies investigating this dissociation in dementia or similar patient populations indicate that these forms of priming may differ in their neural bases. The current study looks at degree of handedness as a way of investigating inferred neural architecture supporting these two forms of priming. A growing body of research indicates that degree of handedness (consistent, or CH, versus inconsistent, or ICH) is associated with greater interhemispheric interaction and functional access to right hemisphere processing in ICH, with superior performance seen in ICH on memory tasks reliant on this processing. Arguments about the theoretical mechanisms underlying identification and production forms of perceptual priming tasks suggest that performance on these tasks will differ as a function of degree of handedness. We tested this question in a group of CH and ICH young adults, who were asked to study lists of words prior to performing a production priming task (word stem completion), a perceptual word identification task, and a word stem cued recall task. While both handedness groups exhibited reliable priming across tasks, word stem completion priming was greater in ICH than CH participants, with identification priming not differing between groups. This dissociation supports the argument that production and identification forms of priming have different underlying neural bases.